2019
DOI: 10.4269/ajtmh.17-0628
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania spp. Infection Rate and Feeding Patterns of Sand Flies (Diptera: Psychodidae) from a Hyperendemic Cutaneous Leishmaniasis Community in Panamá

Abstract: American cutaneous leishmaniasis (ACL) is a common and important vector-borne parasitic zoonosis in Panamá. Here, we study Leishmania spp. infection rates and blood-feeding patterns among common sand flies in Trinidad de Las Minas, a rural community with hyperendemic ACL transmission, and where a deltamethrin fogging trial was performed. Sand flies were collected from April 2010 to June 2011 with light traps installed inside and in the peridomicile of 24 houses. We restricted our analysis to the most abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
0
12
0
1
Order By: Relevance
“…The resulting values are “coordinates”, including centroids for all levels from the different categorical variables considered in the analysis. The centroids are plotted in two dimensions, thus allowing for the evaluation of associations between categories from different variables [ 15 , 46 ]. Associations are stronger as categories from different variables are together but farther apart from the origin (coordinates 0, 0 in the 2D plot), which is the geometric point where random associations are expected to appear [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The resulting values are “coordinates”, including centroids for all levels from the different categorical variables considered in the analysis. The centroids are plotted in two dimensions, thus allowing for the evaluation of associations between categories from different variables [ 15 , 46 ]. Associations are stronger as categories from different variables are together but farther apart from the origin (coordinates 0, 0 in the 2D plot), which is the geometric point where random associations are expected to appear [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although the majority of the species are exophilic, some of them may be attracted by low-intensity light and, thus, enter livestock buildings or shelters [76]. Various studies, notably from South America and Asia, report that pigs appear to be among the preferred hosts for certain sand fly species [77][78][79][80]. A study in China reported high numbers of engorged sand flies on pigs and hypothesized that soil enriched with organic matter in pig pens could be an appropriate substrate for their larval development [81].…”
Section: Phlebotominaementioning
confidence: 99%
“…In Panamá, approximately 37,576 cases of CL have been reported from 2000 to 2019, with the peak of cases registered in 2006 (3774 cases) and 2010 (3221 cases). Provinces of Bocas del Toro (29%), Cocle (16%), Panamá Oeste (16%), and Colón (11%) are the areas with the highest transmission and infection risk [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These sand flies inhabit a range of different environments, and Leishmania transmission depends on the overlap between vector, mammalian reservoir hosts, and human populations [ 5 , 13 , 14 ]. In some regions, the presence of vector species in the human environment may be associated with the emergence of autochthonous cases of leishmaniasis [ 15 , 16 ], as occurs in the Western Panamá Province, where CL is widespread [ 3 ]. It is of epidemiological interest to understand how both land use and seasonality impact sand fly species’ diversity and composition.…”
Section: Introductionmentioning
confidence: 99%